Perhitungan Faktor Perlipatan Neutron dan Fluks Neutron di dalam Reaktor Berbahan Bakar 0235 dengan Teori Difusi. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan Universitas Gajah Mada, 1999)
ABTRAKS The determination of neutron multiplication factor and distribution of neutron in the reactor core are very important in the design process and operation of the reactor, because the neutron multiplication factor and the neutron distribution influent the reactor safety, the control function, and the nuclear fuel management. The scope of work of this research, includes mathematic analysis, numeric Analysis, and program construction. The subject of the computer program is the calculation of the flux infinite medium, calculation of the fission source, the calculation of the neutron multiplication factor, and the neutron distribution. From the calculation using four group diffusion theory for a homogeneous reactor with mixture of 0235 and water, cube shaped with 100 cm of each sides and surrounded by water reflector with 20 cm thickness, the critical mass of the reactor is found to be 11,89 kg. The average of the flux neutron group 1, group 2, group 3, and group 4 were 1,99E+12, 2,41E+12, 2,30E+12, and 8,79E+12 (n/cm2.det) respectively. The maximum flux of all group was in the centre of the core. Key Word : Reaksi pembelahan neutron, harga fluks neutron